SOSIALISASI HUKUM TENTANG BULLYING DI SEKOLAH DASAR NEGERI 1 DESA DONGKO: UPAYA PENCEGAHAN MELALUI EDUKASI DINI BERBASIS KESADARAN HUKUM - Rifki Rifki; Tri Astuty Posumah; Bahtiar Tamrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Bullying can have serious consequences for a child's mental and social development and can even lead to legal violations. Unfortunately, elementary school students' understanding of the legal aspects of bullying is still minimal. This activity aims to promote an early understanding of the legal aspects of bullying among students, teachers, and parents at SD Negeri 1 Dongko Village. The activity methods include interactive legal counseling, case simulations, and group discussions designed to provide a practical understanding of the legal consequences of bullying. The activity results indicate an increase in students' legal awareness of bullying, teachers' and parents' concern for creating a safe learning environment, and an emerging school commitment to preventing and handling bullying based on justice and child protection principles. Thus, this community service activity contributes to building a more child-friendly school culture, oriented towards preventing violence, and supporting students' healthy and dignified growth and development.